Evaluasi Kualitas Produk Tas Ransel Berbasis Pendekatan Ishikawa Diagram dan Failure Mode and Effect Analysis - Frido Yulsandi; Nina Mahbubah (Universitas Putera Batam, 2022)
HHH is a Home Industry that produces various bags. Maintaining sustainable quality is challenging for a firm’s management as bags are considered a product with a competitive market. Problem identification as a fieldwork result found that product defects have been considered a significant problem in managing quality. This study aims to evaluate factors that cause defects and provide suggestions for improvements. This research begins with a walk-through survey and in-depth interview. It then uses these tools in identifying problems using 5M. In addition, tools to use in identifying cause and effect using the Ishikawa diagram. The next stage is to design a questionnaire and then filled by the owner and the head of quality control. This questionnaire result is used to identify severity, occurrence, and detection. This study found three types of defects: Stitching Defects with an RPN value of 343, Accessories Defects at RPN 336, and Torn Defects with an RPN of 253. In addition, redesigning and expanding the workshop is a necessary highlight recommendation for improvement. The following recommendation scenario is that the company owner supervises workers, raw materials, and machine maintenance to maintain product quality.